Factors Affecting the Effectiveness of Implementing Special Autonomy in West Papua Province - Dance Yulian Flassy (Syntax Corporation Indonesia, 2022)
In the implementation of special autonomy, there are crucial actual conditions, with the stipulation of 2% of the general allocation fund ending, the central authority for regional expansion, the establishment of a special autonomous body without involving the Papuan People's Assembly and the Papua Regional Representative Council, new regional autonomy funds and people's welfare is still not yet involved. in accordance with the objectives of the effective implementation of West Papua's special autonomy.This study uses the Convergent Parallel Mixed Methods research design, explained by binomial logit analysis. The sample used is 114 respondents, using stratified random sampling method. The results of his research that the implementation of West Papua's special autonomy based on the political-legal-economic aspects, socio-cultural aspects, and monitoring-evaluation aspects are still not effective, it can be accepted that by strengthening the political-legal-economic, socio-cultural, and in the field of monitoring-evaluation, the implementation of special autonomy will be more effective. Meanwhile, the implementation of special autonomy is due to factors from the central and regional governments as factors that have not been effective in the implementation of special autonomy so that by strengthening central and regional administrators, the implementation of special autonomy will be more effective.The discovery of theories related to the factors that affect the effectiveness of the implementation of West Papua's special autonomy, consists of three aspects, namely: political-legal-economic aspects; socio-cultural aspects; and aspects of monitoring-evaluation. These three aspects must go hand in hand so that the implementation of special autonomy can be even more effective. The findings of the model, namely the functional model, aspects and indicators that affect the implementation of special autonomy; and a model of the structure of a special agency as a working group for the implementation of special autonomy.